A target-oriented algorithm for maintaining serum calcium stability automatically in regional citrate anticoagulation. Issue 8 (August 2021) - Sheng, Ruan-Mei; Zhao, Wen-Biao; Huang, Li-Hong; Chen, Jian-Qin; Dai, Zhen-Juan; Wang, Xue-Min
Background: Regional citrate anticoagulation (RCA) for renal replacement therapy is widely practiced in critically ill patients. However, concern exists regarding its labor-intensiveness for monitoring and the associated hypocalcemia. In this study, we provided an algorithm for prescribing RCA and evaluated its safety in patients. Methods: During 18 hemofiltration treatments with calcium-free replacement solution, participants were randomized to receive algorithm-based or trial-and-error RCA protocol. The effluent volume, post-filter and in vivo ionized calcium (iCa), and calcium in the sera and effluents were periodically measured at an interval of 1 to 2 h. Results: For patients received algorithm-based RCA protocol, no one had a serum iCa less than 0.9 mmol/L, and none needed calcium supplement adjustment to maintain serum calcium stability. For patients accepted trial-and-error protocol, all patients had a serum iCa below 0.9 mmol/L, their serum iCa and calcium levels fluctuated dramatically, and all patients need additional calcium supplement adjustment during RCA. None of the participants showed a post-filter iCa > 0.4 mmol/L. Conclusion: We provided a safe algorithm for calculating calcium supplementation doses that could maintain serum calcium stability without additional adjustment during RCA.